Effects of mechanism of injury and patient age on outcomes in geriatric rib fracture patients. Issue 1 (16th March 2017) - Shi, Helen H; Esquivel, Micaela; Staudenmayer, Kristan L; Spain, David A
Abstract : Background: Patients older than 65 years have 2–5 times higher mortality if they sustain ≥2 rib fractures compared to younger adults. As a result, our level I trauma center guidelines suggest that older adults with rib fractures be admitted to the intensive care unit for the first 24 hours. In this study, we evaluated the outcomes associated with these guidelines. Methods: We retrospectively reviewed all patients aged ≥65 years in our Trauma Registry who sustained rib fractures from January 2008 to March 2015. Data included demographics, comorbidities, injuries, length of intensive care and hospital stay (LOS), ventilator days, analgesic used, morbidity, mortality, and disposition. Results: 97 patients aged ≥65 years with at least one rib fracture and an Abbreviated Injury Score of ≤2 for other regions were admitted. Falls caused 58% of the injuries, while motor vehicle collisions (MVC) accounted for 33%. Overall mortality was 4%. Patients who fell had a median hospital LOS that was 0.5 to 1 day longer than in those who suffered other mechanisms of injury or were involved in an MVC respectively. Patients aged ≥70 years had a median LOS of 4 days, twice that of those aged 65 to 69 years. Of the 87 patients with more than one rib fracture, 59 (68%) were not admitted directly to the intensive care unit (ICU) from the emergency department as recommended by our guidelines. 6 of these 59 patients (9%) were later transferred to the ICU and 2 of these patients expired. Conclusions: Although overall compliance with the geriatric rib fracture guideline was low, both mortality and hospital LOS were low in this group. This suggests that the guideline could be modified to reduce ICU resource usage without compromising patient outcomes. Level of evidence: Level III, retrospective cohort study.